Investors´ protection in the U.S.: the issue of mandatory arbitration clauses in contracts between investors and brokerage/advisory firms - DÉBORA CHAVES MARTINES FERNANDES (Revista Direito GV)
Abstract This paper proposes a review of the American literature, as well as the main rulings of Supreme Court of United States, aiming to map the pros and cons of inserting a mandatory pre-dispute arbitration clause in contracts between investors and brokerage/advisory firms that trade on the securities market. The study discusses some proposals to banish this sort of clause and some ideas to reach a middle ground solution.